The Effects of topical anesthetic on swallowing during nasoendoscopy. (2nd April 2013) - Lester, Scott; Langmore, Susan E.; Lintzenich, Catherine R.; Wright, S. Carter; Grace‐Martin, Karen; Fife, Tim; Butler, Susan G.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To assess the effects of a typical otolaryngologic dose of 1 mL of 4% lidocaine on penetration aspiration scale scores and participant discomfort during flexible endoscopic evaluation of swallowing. Study Design A prospective pilot study. Methods Twenty healthy participants consumed 12 swallows consisting of graduated volumes of milk, water, pudding, and cracker in anesthetized and nonanesthetized conditions. Each participant was randomly selected to begin with the anesthetized or nonanesthetized condition. Each participant returned within 7 days to repeat the study in the other condition. Digital recordings of their evaluations were scored via the penetration‐aspiration scale in a blinded fashion. Participants recorded their discomfort and tolerance of each flexible endoscopic evaluation of swallowing. Results The anesthetized condition yielded significantly worse swallowing function (P = .001) than the nonanesthetized condition. The nonanesthetized condition yielded greater discomfort and pain during the procedure (P = .006, .018), greater pain during insertion and removal of the endoscope (P = .002, .003) and less overall tolerance (P = .016) than the anesthetized condition. Conclusions A typical otolaryngologic anesthetic dose of 1 mL of 4% lidocaine during flexible endoscopic evaluation of swallowing predisposed healthy young adults to higher penetration aspiration scale scores (less safe swallowing) than the nonanesthetized condition; however, the anesthetic reduced discomfort and provided better overall tolerance. Future studies need to evaluate the effects of lower doses of lidocaine (0.2 and 0.5 mL) on swallowing function and comfort. Level of Evidence 4. Laryngoscope, 2012